Interrogating The shield - Ray, Nicholas, 1975- (Television and popular culture., 2012)
When The Shield first appeared on U.S. television in March 2002, it broke ratings records with the highest audience-rated original series premiere in cable history. In the course of its subsequent seven-season run, the show went on to win international acclaim for its abrasive depiction of an urban American dystopia and the systemic political and juridical corruption feeding it. This book, dedicated to the analysis of this immensely successful series, brings together ten critical essays written from a variety of methodological and theoretical perspectives. Topics range from an exploration of the series' derivation, genre, and production, to expositions of the ethics, aesthetics, and politics of the show.